La sobreprotección de los padres en la formación de los niños de primer año de Educación general básica, paralelo "a" de la unidad educativa Pedro Vicente Maldonado de la ciudad de Riobamba, provincia de Chimborazo, período lectivo 2014-2015. - Carrasco Agualongo, Jessica Maricela (2017)
The objective of this is research is to determine the relationship between overprotection of parents and the formation of children of the first year of Basic General Education. Parallel "A" of the Educational Unit in the academic period 2014-2015, it was evident that overprotection in children is harmful so that they can develop not only in the school but also in the home and therefore in society , the methodology in which the type of research was field, transversal and bibliographical, of non-experimental and descriptive design was used because it was worked in said institution in a determined time, with a descriptive design described the two variables as the overprotection and the formation of children, and with a population of 30 students which is divided into 12 girls and 18 children, the sample with which work was intentional since the population was not manipulated, the technique used was the tokens of observation, the instruments were the same questionnaires that helped us in the analyzes and results obtained, the conclusions and recommendations were made in ba the objectives and results obtained, where it was possible to show that overprotection influences the formation of children, making them fearful and insecure of themselves.